Evaluation of 6 candidate genes on chromosome 11q23 for coeliac disease susceptibility: a case control study - Feighery, Conleth; Trimble, Valerie; Kennedy, Nicholas; Mc Manus, Ross; Kelleher, Dermot; O'Morain, Colm (My University, 2010)
BACKGROUND: Recent whole genome analysis and follow-up studies have identified many new risk variants for coeliac disease (CD, gluten intolerance). The majority of newly associated regions encode candidate genes with a clear functional role in T-cell regulation. Furthermore, the newly discovered risk loci, together with the well established HLA locus, account for less than 50% of the heritability of CD, suggesting that numerous additional loci remain undiscovered. Linkage studies have identified some well-replicated risk regions, most notably chromosome 5q31 and 11q23. METHODS: We have evaluated six candidate genes in one of these regions (11q23), namely CD3E, CD3D, CD3G, IL10RA, THY1 and IL18, as risk factors for CD using a 2-phase candidate gene approach directed at chromosome 11q. 377 CD cases and 349 ethnically matched controls were used in the initial screening, followed by an extended sample of 171 additional coeliac cases and 536 additional controls. RESULTS: Promotor SNPs (-607, -137) in the IL18 gene, which has shown association with several autoimmune diseases, initially suggested association with CD (P < 0.05). Follow-up analyses of an extended sample supported the same, moderate effect (P < 0.05) for one of these. Haplotype analysis of IL18-137/-607 also supported this effect, primarily due to one relatively rare haplotype IL18-607C/-137C (P < 0.0001), which was independently associated in two case-control comparisons. This same haplotype has been noted in rheumatoid arthritis. CONCLUSION: Haplotypes of the IL18 promotor region may contribute to CD risk, consistent with this cytokine's role in maintaining inflammation in active CD.
PUBLISHED
PMID: 20478055, * Equal contribution
Keywords: coeliac disease; candidate gene; genomics; Genes & Society; Immunology, Inflammation & Infection